Influence of addition of [2-(methacryloyloxy)ethyl]trimethylammonium chloride to an experimental adhesive - Fabrício Mezzomo COLLARES; Vicente Castelo Branco LEITUNE; Patrícia FRANKEN; Clarissa Fatturi PAROLLO; Fabrício Aulo OGLIARI; Susana Maria Werner SAMUEL (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract The aim of this study was to develop an experimental adhesive with addition of [2-(methacryloyloxy)ethyl]trimethylammonium chloride (METAC) and to evaluate its mechanical and biological properties and its in vitro antibacterial activity. An experimental adhesive resin was formulated with Bis-GMA, TEGDMA, and HEMA. The antibacterial monomer was added at concentrations of 1%, 2.5%, and 5% (METAC groups). A group without METAC addition was used as control. The experimental adhesives were evaluated as to their antibacterial potential against Streptococcus mutans, degree of conversion, and softening in ethanol for 2 hours. The data were analyzed by one-way ANOVA, Tukey's post-hoc test, and the paired Student's t-test (significance level of 0.05). METAC showed antibacterial activity against S. mutans at all concentrations (p < 0.05). There was no statistical difference across METAC groups (p > 0.05). The 1%, 2.5%, and 5% groups yielded the highest mean values for degree of conversion (p < 0.05). The 1% group did not differ from the control group (p > 0.05). There was no statistical difference in baseline microhardness values (p > 0.05) and microhardness values after immersion in ethanol were lower than at baseline for all groups (p < 0.05). There was no statistical difference in the reduction of Knoop hardness number (KHN) after immersion in ethanol for any of the groups (p > 0.05). The results of the present study indicate that METAC is a promising antibacterial agent when added to an adhesive system.